2021
DOI: 10.3389/fcell.2021.645658
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-14 Promotes Trophoblast Migration and Invasion by Upregulating the Expression of MMP-9 and N-Cadherin

Abstract: Galectin-14 is specifically expressed in placental trophoblasts, and its expression is reduced in trophoblasts retrieved from the cervix of women destined to develop early pregnancy loss. However, the roles of galectin-14 in regulating trophoblasts and in the pathogenesis of pregnancy complication have never been investigated. In the current research, we aimed to investigate the roles of galectin-14 in the regulation of trophoblasts. Tissues of the placenta and villi were collected. Primary trophoblasts and hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
0
17
1
2
Order By: Relevance
“…Enhanced Cx43 level is also correlated with the promotion of cell migration in tumor contexts [59–61]. N‐cadherin is not only one of the hallmarks of the EMT switch in tumorigenesis and metastasis [62], but its role in promoting primary trophoblast and HTR‐8/SVneo cell migration [63] and invasion [64] has also been demonstrated. The importance of MMP9 in trophoblastic cell migration and invasion, and its dysregulation in complicated pregnancies, has been the subject of intense research.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced Cx43 level is also correlated with the promotion of cell migration in tumor contexts [59–61]. N‐cadherin is not only one of the hallmarks of the EMT switch in tumorigenesis and metastasis [62], but its role in promoting primary trophoblast and HTR‐8/SVneo cell migration [63] and invasion [64] has also been demonstrated. The importance of MMP9 in trophoblastic cell migration and invasion, and its dysregulation in complicated pregnancies, has been the subject of intense research.…”
Section: Discussionmentioning
confidence: 99%
“…Absent from this list is MMP9, a matrix metalloprotease often described as an EVT marker important in controlling trophoblast invasion [55]. It should be noted that the majority of (if not all) studies describing MMP9 expression specificity to invasive trophoblast subsets characterized and tested MMP9 function in immortalized trophoblastic cell lines [56] or inadequately described primary trophoblast cultures [57]. This latter example is especially important as primary cultures of CTB and EVT are challenging to establish and experiment on.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analysis showed that treatment with galectin-1 induced upregulation of genes encoding matrix metalloproteinases MMP-1, MMP-10, MMP-12 and tissue fibrinogen activator in dendritic cells, which was associated with increased migratory activity of these antigen-presenting cells ( 71 ). In addition, transfection of galectin-4cDNA into placental trophoblast cells induced enhanced Akt phosphorylation upregulated the expression of MMP-9 and N-Cadherin, promoting trophoblast migration and invasion ( 72 ).…”
Section: Proliferation and Migrationmentioning
confidence: 99%